2017
DOI: 10.1111/cts.12487
|View full text |Cite
|
Sign up to set email alerts
|

Oral Apolipoprotein A‐I Mimetic D‐4F Lowers HDL‐Inflammatory Index in High‐Risk Patients: A First‐in‐Human Multiple‐Dose, Randomized Controlled Trial

Abstract: A single dose of the apolipoprotein (apo)A‐I mimetic peptide D‐4F rendered high‐density lipoprotein (HDL) less inflammatory, motivating the first multiple‐dose study. We aimed to assess safety/tolerability, pharmacokinetics, and pharmacodynamics of daily, orally administered D‐4F. High‐risk coronary heart disease (CHD) subjects added double‐blinded placebo or D‐4F to statin for 13 days, randomly assigned 1:3 to ascending cohorts of 100, 300, then 500 mg (n = 62; 46 men/16 women). D‐4F was safe and well‐tolerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 43 publications
(108 reference statements)
1
49
0
1
Order By: Relevance
“…The daily application of single doses of D-4F reduced their HDL-inflammatory index. 14 In this study as well as previously, a single dose of D-4F injected locally lasted 6 h to inhibit inflammatory and capsaicin-induced pain. 5 For clinical use, a longer duration of action would be necessary.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The daily application of single doses of D-4F reduced their HDL-inflammatory index. 14 In this study as well as previously, a single dose of D-4F injected locally lasted 6 h to inhibit inflammatory and capsaicin-induced pain. 5 For clinical use, a longer duration of action would be necessary.…”
Section: Discussionsupporting
confidence: 69%
“…occurring in atherosclerotic plaques and pro-inflammatory reactions. [13][14][15] In this study, the efficacy of D-4F is tested in a rodent model of neurogenic inflammation, induced by capsaicin, evoking hypersensitivity and TRP channel activity. We found that D-4F ameliorated capsaicin-induced mechanical but not TRPV1-typical thermal hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…plates, was recorded. The peptide and its derivatives form nanodiscs of similar size and shape as that of the apolipoprotein (51), and it has been extensively studied for its lipidassociating and numerous favorable properties when tested in biomedical assays, including anti-atherosclerosis, antisepsis, anti-Alzheimer's, and antidiabetic properties (30,31,52). When the alanine-5 position is labeled with 15 N and the peptide is reconstituted into POPC membranes, the chemical shifts are 80 ppm for concentrations of 1 and 2 mol%, a value that shifts to $90 ppm at 3.8 and 10 mol% ( Fig.…”
Section: Figurementioning
confidence: 99%
“…When tested in mice 18A and its analogs, it showed anti-inflammatory properties and ameliorated several lipid-mediated inflammatory diseases (30). A D-amino-acid analog of the peptide has been shown to be orally bioactive, resulting in improvements in high-density lipoprotein (HDL) function (31).…”
Section: Introductionmentioning
confidence: 99%
“…The potential for development of full-length HDLassociated apolipoproteins such as apoA-I or apoE as therapeutics is limited by their size, structure, and posttranslational modifications, making small HDL mimetic peptides, such as 4F, attractive candidates in this regard. Notably, unlike other HDL mimetic peptides (Leman et al 2014;White et al 2014), 4F has been tested in three human clinical trials with 50, 152, and 62 individuals, respectively, for cardiovascular disease; 4F was found to be safe and welltolerated when administered orally or by injections, and improved HDL anti-inflammatory properties (Bloedon et al 2008;Watson et al 2011;Dunbar et al 2017). Furthermore, our finding that D-4F improves apoE secretion and lipidation to the same extent as 4F has significant implications for therapeutic development, because D-4F is orally bioavailable with a longer half-life than L-4F in vivo (Navab et al 2005).…”
Section: Discussionmentioning
confidence: 99%